2016
DOI: 10.3390/w8010026
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Texture and Erodibility for Sediment Retention in Receiving Basins of Coastal Louisiana Diversions

Abstract: Abstract:Although the Mississippi River deltaic plain has been the subject of abundant research over recent decades, there is a paucity of data concerning field measurement of sediment erodibility in Louisiana estuaries. Two contrasting receiving basins for active diversions were studied: West Bay on the western part of Mississippi River Delta and Big Mar, which is the receiving basin for the Caernarvon freshwater diversion. Push cores and water samples were collected at six stations in West Bay and six statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Through filtration of collected turbidity solutions, we measured the eroded mass for each imposed shear stress, which is used to generate eroded mass curves for each experimental sediment mixture. More methodological details can be found in Xu et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Through filtration of collected turbidity solutions, we measured the eroded mass for each imposed shear stress, which is used to generate eroded mass curves for each experimental sediment mixture. More methodological details can be found in Xu et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Low trapping efficiencies of 0.10-0.20 have been reported by Syvitski et al (2009) for small, steep-gradient rivers and efficiencies of 0.50-0.60 for larger deltas with multiple distributary channels. Multiple studies on sediment retention have reported sediment trapping efficiencies between 0.27 and nearly 1.0 for Mississippi and Atchafalaya diversion systems (Xu et al 2016), where the trapping efficiency was higher further from the coast (Roberts et al 2015;Xu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are only a handful of studies that have attempted to tie the bulk sedimentary properties of a recent deposit to sedimenttransport properties in the river that created it (Törnqvist et al, 2007;Kim et al, 2009;Giosan et al, 2013;Day et al, 2016), and we are unaware of any with a subsurface data set as rich as the one available for the ACS. While many workers have published on the "river side" issues concerning diversions, including the sediment available (Kesel, 1988;Blum and Roberts, 2009;Allison et al, 2012) and the physics of extracting sediment from the trunk channel (Allison and Meselhe, 2010;Meselhe et al, 2012;Nittrouer et al, 2012a;Allison et al, 2013), only recently have researchers begun to investigate "basin side" issues that impact SRE (Xu et al, 2016). The availability of detailed sediment-transport data from the modern Lower Mississippi River (LMR) (Allison et al, 2012) provides a unique opportunity to connect fluvial sediment budgets to the sediments preserved in the delta.…”
Section: Measuring Sediment Retention Efficiencymentioning
confidence: 99%